INTEGRATION OF FRED R. DAVID’S STRATEGIC FRAMEWORK AND THE BALANCED SCORECARD IN MANAGEMENT ACCOUNTING PRACTICES FOR COMPETITIVE ADVANTAGE: A MULTIPLE CASE STUDY OF MEDIUM SCALE MANUFACTURING FIRMS IN EAST JAVA - Samsul Huda; Ahmad Suminto; Achmad Luthfi Chamidi (Universitas Tulungagung, 2025)
This study aims to analyze strategic management in management accounting practices to achieve competitive advantage in Indonesian manufacturing companies. The object of study is medium-scale manufacturing firms focusing on Balance Scorecard (BSC) based strategic planning and SWOT analysis. The method employed is a qualitative descriptive approach through in-depth interviews with accounting and strategy managers (n=10), observation of financial reports, and content analysis of secondary data from annual reports. Findings reveal that BSC integration in financial and internal process perspectives enhances management accounting effectiveness by 25% in strategic decision making, while SWOT analysis identifies product portfolio strengths and market expansion opportunities as key drivers of competitive advantage. The conclusion states that aggressive strategies based on BSC and SWOT are effective for manufacturing firms facing intense competition, with recommendations for QSPM implementation in prioritizing functional strategies.